Integrating Fiqhiyyah Legal Maxims and Positive Law Principles in the Formation of Indonesia's New National Criminal Code - Ahmad Agus Ramdlany; Ahmad Musadad; Hammis Syafaq; Maher Ali Ahmad Al-Khaldi; Saleem Asouli (PT. Islamic Research Publiser, 2026)
Although Indonesia is not formally constituted as an Islamic state, Islamic legal values have significantly influenced the development of its national legal system, particularly in the formation of modern legislation. This study aims to examine the integration of fiqhiyyah legal maxims into the foundational principles of Law No. 1 of 2023 concerning Indonesia's New National Criminal Code (KUHP). Employing a qualitative approach grounded in normative juridical methods, this research draws upon primary legal documents, classical fiqh literature, and contemporary legal scholarship. Data were collected through a systematic literature review and analysed using conceptual and statutory approaches to identify patterns of normative convergence and doctrinal alignment. The findings indicate that at least eight fiqhiyyah legal maxims are substantively embedded within the core principles of the KUHP. Notably, the maxim la jarimata wa la 'uqubata illa bi al-nass corresponds to the principle of legality as stipulated in Articles 1(1) and 2(1). The principle of non-retroactivity is reflected in la raj'iyyah fi al-tashri' al-jina'i, while the doctrine of limited retroactivity aligns with inna al-tashri' al-jina'i yajuzu an yakuna lahu atharun raji'un as reflected in Article 3(1). Furthermore, the maxim inna al-shari'ah al-islamiyyah tutabbaqu' ala kulli jarimah underpins the principles of active and passive nationality in Articles 5 and 8. This study contributes to the discourse on legal pluralism by demonstrating that Indonesia's criminal law reform embodies a substantive harmonisation between positive Law and Islamic legal reasoning. It highlights the epistemological relevance of fiqhiyyah maxims as a normative bridge in shaping a responsive, adaptive, and contextually grounded modern legal system in a pluralistic society.